A Call for Critical Intersectional Religious Literacies: An Intersectional Examination of Whiteness and Christian Privilege in Teacher Education. Issue 2 (3rd April 2021) - Aronson, Brittany; Altowajri, Muna A.; Brown, Dominique M.; Enright, Esther A.; Stohry, Hannah R.
Abstract: This study contributes to our understanding of how pre-service teachers engage in courses that discuss racism, whiteness, Christian privilege, and religious diversity. First, we contextualize the racialization of religion in U.S. society and describe the literature distinguishing Christian privilege, hegemony, and whiteness, as well as what is known about teachers' understanding of religion. Second, we present our theoretical framework, which is informed by intersectionality theory and critical whiteness studies. Third, we share the findings from our longitudinal study of pre-service teacher coursework. Finally, we conclude with implications and recommendations for increased religious literacies within teacher education.